Preparation method of high-temperature-resistant toughened polymer composite material
Through the composite modification of end-hydroxyl liquid nitrile rubber, rosin anhydride modified epoxy soybean oil and plasma-modified aramid fiber, the toughness and impact resistance of phenolic resin materials are solved, and the impact strength and resistance of the material are improved High temperature performance, forming a chemical bonding network, significantly enhancing the compatibility and thermal stability of the material.
Patent Information
- Application Number
- CN202411310719.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The phenolic resin materials have poor toughness and poor impact resistance, and the reaction activity of epoxy soybean oil and phenolic resin is low, making it difficult to effectively toughen. The polar groups and low surfactivity of aramid fibers lead to poor compatibility. , it is difficult to achieve enhanced effect.
Combined modification is made by end-hydroxyl liquid nitrile rubber, rosin anhydride modified epoxy soybean oil and plasma modified aramid fiber. The oxygen-containing groups such as hydroxyl groups are introduced through air plasma technology to catalyze the rosin maleic anhydride and Epoxy soybean oil reacts to form rosin anhydride modified epoxy soybean oil, improves the compatibility and crosslinking of materials, and forms a chemical bonding network.
The impact strength, bending strength and high temperature resistance of the composite material are significantly improved, the toughness and thermal decomposition temperature of the material are enhanced, the high-temperature mass surplus rate is improved, and the compatibility and interface bonding strength of the material are enhanced.
Smart Images

Figure BDA0005050607940000031 
Figure BDA0005050607940000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phenolic resins, in particular to a method for preparing a high-temperature resistant toughened polymer composite material. Background Art
[0002] Phenolic resin has good wear resistance, chemical resistance and flame retardancy, and is widely used in anti-corrosion materials, adhesives, grinding wheel manufacturing and other fields. However, phenolic resin has poor toughness and poor impact resistance. Currently, nitrile rubber, cardanol, epoxy soybean oil, high-performance fiber and other materials are mainly used to toughen and strengthen phenolic resin.
[0003] Epoxidized soybean oil has the advantages of being green, environmentally friendly, cheap, easily available, and having good toughening effects. Although epoxidized soybean oil contains multiple epoxy groups, without the addition of a catalyst, the reaction activity of epoxidized soybean oil with phenolic resin is low, the grafting is difficult, and the toughening effect on phenolic resin is not good.
[0004] Aramid fiber has excellent mechanical strength, modulus and high temperature resistance, and is widely used in polymer materials. However, aramid fiber lacks polar groups, has low surface activity, and has poor compatibility with polymer materials, making it difficult to effectively exert the reinforcing effect of aramid fiber. The present invention improves the toughness, impact strength and high temperature resistance of phenolic resin materials by using hydroxyl-terminated liquid nitrile rubber, rosin anhydride-modified epoxy soybean oil, and ionomer-modified aramid fiber. Summary of the invention
[0005] The invention solves the problems of poor toughness and poor impact resistance of the phenolic resin material and improves the high temperature resistance of the phenolic resin material.
[0006] The technical scheme of the present invention is: a high temperature resistant toughened polymer composite material, comprising the following raw materials by weight: 60-86 parts of phenolic resin, 8-20 parts of hydroxyl-terminated liquid nitrile rubber, 4-15 parts of rosin anhydride modified epoxy soybean oil, and 2-5 parts of plasma modified aramid fiber;
[0007] The preparation method of the high-temperature resistant toughened polymer composite material is as follows: phenolic resin, terminal hydroxyl liquid nitrile rubber, rosin anhydride modified epoxy soybean oil, and plasma modified aramid fiber are added into a high-speed mixer, and after mixing, the materials are poured into a mold for co-curing to obtain the high-temperature resistant toughened polymer composite material.
[0008] Furthermore, the mixing temperature is 50-70° C., and the mixing time is 1-3 h.
[0009] Further, the co-curing is firstly cured at 80-90°C for 2-5h, then cured at 100-120°C for 2-3h, and finally cured at 130-150°C for 2-3h.
[0010] Furthermore, the preparation method of rosin anhydride modified epoxy soybean oil is as follows: add rosin maleic anhydride adduct and catalyst tetrabutylammonium bromide to epoxy soybean oil, stir and mix well, and react, and control the reaction temperature to be 90-100°C; during the reaction, measure the acid value every 1 hour, and when the acid value of the reaction system is 6-8 mg / KOH, terminate the reaction and cool the material to obtain rosin anhydride modified epoxy soybean oil.
[0011] Furthermore, the masses of rosin maleic anhydride adduct and tetrabutylammonium bromide are 165-205% and 1.4-2% of the mass of epoxidized soybean oil, respectively.
[0012] Furthermore, the preparation method of plasma-modified aramid fiber is as follows: the aramid fiber is placed in a reaction chamber of a cold plasma generator, the reaction chamber is evacuated and then air is introduced, the pressure is controlled to be 40-70Pa, and then the output power of the plasma power supply is adjusted to 60-120W, and plasma treatment is performed for 2-6 minutes to obtain plasma-modified aramid fiber.
[0013] The technical effect of the present invention is as follows: the present invention uses air plasma technology to modify aramid fiber, and introduces a large number of oxygen-containing groups such as hydroxyl groups on the surface of the aramid fiber. Then, tetrabutylammonium bromide is used as a catalyst to catalyze the reaction between the carboxyl group of rosin maleic anhydride adduct and the epoxy group of epoxidized soybean oil to obtain rosin anhydride modified epoxidized soybean oil, thereby introducing rosin condensed rings and anhydride groups into the molecular chain of the epoxidized soybean oil.
[0014] The present invention utilizes terminal hydroxyl liquid nitrile rubber, plasma modified aramid fiber and rosin anhydride modified epoxy soybean oil to carry out composite modification on phenolic resin. The rosin anhydride modified epoxy soybean oil contains a large number of active anhydride groups. In the process of high-temperature co-curing, the anhydride groups can react with the terminal hydroxyl groups of the liquid nitrile rubber, the hydroxyl groups on the surface of the modified aramid fiber and the phenolic hydroxyl groups of the phenolic resin, so that the nitrile rubber, the aramid fiber and the phenolic resin are chemically bonded through the rosin anhydride modified epoxy soybean oil, and the compatibility of the three interface bonding strength is significantly enhanced. The nitrile rubber itself has excellent toughness, and the aramid fiber has the characteristics of high strength and high modulus, so that the nitrile rubber and the aramid fiber play an excellent toughening and strengthening role, and the composite material has higher impact strength and bending strength.
[0015] The rosin anhydride modified epoxy soybean oil of the present invention contains a flexible soybean oil molecular chain, which can also play a toughening effect on the phenolic resin, further improving the toughness and impact strength and other properties; and it contains a heat-resistant rosin condensed ring structure, and the rosin condensed ring structure is chemically grafted and bonded to the side chain of the phenolic resin, which has a significant effect on improving the thermal decomposition temperature and high-temperature mass residual rate of the phenolic resin. At the same time, a chemical cross-linking network is formed between the phenolic resin and the high-temperature resistant aramid fiber, etc., which improves the cross-linking degree between the molecular chains and can further improve the high-temperature resistance of the composite material. DETAILED DESCRIPTION
[0016] The raw materials used in the examples and comparative examples of the present invention are as follows: the phenolic resin is phenolic resin 2130. The hydroxyl-terminated liquid nitrile rubber is LNBR-820. The carboxyl-terminated liquid nitrile rubber CAS number is 25265-19-4. The epoxy soybean oil CAS number is 8013-07-8. The rosin CAS number is 8050-09-7. The aramid fiber is a short-cut aramid fiber with an average length of 6 mm.
[0017] Mix 30 mmol rosin and 30 mmol maleic anhydride, heat to 200℃, react for 2 hours, cool and discharge to obtain rosin maleic anhydride adduct. The reaction formula is:
[0018]
[0019] Example 1
[0020] To 20 g of epoxy soybean oil, add 33 g of rosin maleic anhydride adduct and 0.28 g of catalyst tetrabutylammonium bromide, stir and mix, then heat to 90 ° C for reaction. During the reaction, the acid value is measured every 1 hour. When the acid value of the reaction system is 6 mg / KOH, the reaction is terminated and the material is cooled to obtain rosin anhydride modified epoxy soybean oil.
[0021] The aramid fiber was placed in the reaction chamber of the cold plasma generator. The reaction chamber was evacuated and then air was introduced. The pressure was controlled to be 50 Pa. Then, the output power of the plasma power supply was adjusted to 120 W. The plasma treatment was performed for 4 minutes to obtain the plasma-modified aramid fiber.
[0022] 860g of phenolic resin, 80g of terminal hydroxyl liquid nitrile rubber, 40g of rosin anhydride modified epoxy soybean oil, and 20g of plasma modified aramid fiber were added to a high-speed mixer and mixed at 60°C for 1h. The materials were poured into a mold and first co-cured at 80°C for 5h, then co-cured at 110°C for 2h, and finally co-cured at 150°C for 2h to obtain a high-temperature resistant toughened polymer composite material.
[0023] Example 2
[0024] To 20 g of epoxy soybean oil, add 36 g of rosin maleic anhydride adduct and 0.33 g of catalyst tetrabutylammonium bromide, stir and mix, then heat to 90 ° C for reaction. During the reaction, the acid value is measured every 1 hour. When the acid value of the reaction system is 8 mg / KOH, the reaction is terminated and the material is cooled to obtain rosin anhydride modified epoxy soybean oil.
[0025] The aramid fiber was placed in the reaction chamber of the cold plasma generator. The reaction chamber was evacuated and then air was introduced. The pressure was controlled to be 70 Pa. Then, the output power of the plasma power supply was adjusted to 60 W. The plasma treatment was performed for 2 minutes to obtain the plasma-modified aramid fiber.
[0026] 750g of phenolic resin, 120g of terminal hydroxyl liquid nitrile rubber, 90g of rosin anhydride modified epoxy soybean oil, and 40g of plasma modified aramid fiber were added to a high-speed mixer, mixed at 70°C for 1h, poured into a mold, first co-cured at 80°C for 5h, then co-cured at 120°C for 2h, and finally co-cured at 130°C for 3h to obtain a high-temperature resistant toughened polymer composite material.
[0027] Example 3
[0028] To 20 g of epoxy soybean oil, add 41 g of rosin maleic anhydride adduct and 0.4 g of catalyst tetrabutylammonium bromide, stir and mix, then heat to 100 °C for reaction. During the reaction, measure the acid value every 1 h. When the acid value of the reaction system is 8 mg / KOH, terminate the reaction and cool the material to obtain rosin anhydride modified epoxy soybean oil.
[0029] The aramid fiber was placed in the reaction chamber of the cold plasma generator. The reaction chamber was evacuated and then air was introduced. The pressure was controlled to be 40 Pa. Then, the output power of the plasma power supply was adjusted to 60 W. The plasma treatment was performed for 6 minutes to obtain the plasma-modified aramid fiber.
[0030] 600 g of phenolic resin, 200 g of terminal hydroxyl liquid nitrile rubber, 150 g of rosin anhydride modified epoxy soybean oil, and 50 g of plasma modified aramid fiber were added into a high-speed mixer and mixed at 50°C for 3 h. The materials were poured into a mold and first co-cured at 90°C for 2 h, then co-cured at 100°C for 3 h, and finally co-cured at 130°C for 3 h to obtain a high-temperature resistant toughened polymer composite material.
[0031] Comparative Example 1
[0032] The main difference between this comparative example and Example 1 is that rosin anhydride-modified epoxidized soybean oil is not added.
[0033] 860 g of phenolic resin, 80 g of hydroxyl-terminated liquid nitrile rubber, and 20 g of plasma-modified aramid fiber were added to a high-speed mixer and mixed at 60°C for 1 h. The materials were poured into a mold and first co-cured at 80°C for 5 h, then co-cured at 110°C for 2 h, and finally co-cured at 150°C for 2 h to obtain a polymer composite material.
[0034] Comparative Example 2
[0035] The main difference between this comparative example and Example 1 is that rosin maleic anhydride adduct is used instead of rosin anhydride-modified epoxidized soybean oil.
[0036] 860 g of phenolic resin, 80 g of terminal hydroxyl liquid nitrile rubber, 40 g of rosin maleic anhydride adduct, and 20 g of plasma-modified aramid fiber were added to a high-speed mixer, mixed at 60°C for 1 hour, poured into a mold, first co-cured at 80°C for 5 hours, then co-cured at 110°C for 2 hours, and finally co-cured at 150°C for 2 hours to obtain a polymer composite material.
[0037] Comparative Example 3
[0038] The main difference between this comparative example and Example 1 is that epoxy soybean oil is used instead of rosin anhydride modified epoxy soybean oil.
[0039] 860 g of phenolic resin, 80 g of terminal hydroxyl liquid nitrile rubber, 40 g of epoxy soybean oil, and 20 g of plasma-modified aramid fiber were added to a high-speed mixer and mixed at 60°C for 1 h. The materials were poured into a mold and first co-cured at 80°C for 5 h, then co-cured at 110°C for 2 h, and finally co-cured at 150°C for 2 h to obtain a polymer composite material.
[0040] Comparative Example 4
[0041] The main difference between this comparative example and Example 1 is that the hydroxyl-terminated liquid nitrile rubber is replaced by carboxyl-terminated liquid nitrile rubber.
[0042] 860 g of phenolic resin, 80 g of terminal carboxyl nitrile rubber, 40 g of rosin anhydride modified epoxy soybean oil, and 20 g of plasma modified aramid fiber were added to a high-speed mixer and mixed at 60°C for 1 h. The materials were poured into a mold and first co-cured at 80°C for 5 h, then co-cured at 110°C for 2 h, and finally co-cured at 150°C for 2 h to obtain a polymer composite material.
[0043] Comparative Example 5
[0044] The main difference between this comparative example and Example 1 is that the plasma-modified aramid fiber is replaced by unmodified aramid fiber.
[0045] Add 860g of phenolic resin, 80g of terminal hydroxyl liquid nitrile rubber, 40g of rosin anhydride modified epoxy soybean oil, and 20g of aramid fiber into a high-speed mixer, mix at 60°C for 1h, pour the materials into a mold, first co-cure at 80°C for 5h, then co-cure at 110°C for 2h, and finally co-cure at 150°C for 2h to obtain a polymer composite material.
[0046] Comparative Example 6 is pure phenolic resin.
[0047] The products of the embodiments and comparative examples were subjected to the following performance tests:
[0048] The bending properties of composite materials are tested according to GB / T9341-2000 method; the impact properties are tested according to GB / T1043.1-2008 method.
[0049] The thermal properties of the polymer composite material were tested by a thermogravimetric analyzer. The test conditions were a nitrogen atmosphere and a heating rate of 10°C / min. The maximum test temperature was 800°C, and the mass residual rate at the maximum test temperature was calculated.
[0050] The specific performance test results are shown in Table 1 below.
[0051] Table 1: Performance test results of the products of the embodiments and comparative examples
[0052]
[0053] It can be seen from the test results of Table 1 that the embodiments of the present invention utilize terminal hydroxyl liquid nitrile rubber, plasma modified aramid fiber, and rosin anhydride modified epoxy soybean oil to carry out composite modification of phenolic resin. After the aramid fiber is modified by air plasma, a large number of oxygen-containing groups such as hydroxyl groups are introduced on the surface of the aramid fiber. Rosin anhydride modified epoxy soybean oil contains a large number of active anhydride groups. In the process of high-temperature co-curing, the anhydride groups can react with the terminal hydroxyl groups of the liquid nitrile rubber, the hydroxyl groups on the surface of the modified aramid fiber, and the phenolic hydroxyl groups of the phenolic resin, so that the nitrile rubber, aramid fiber, and phenolic resin are chemically bonded by rosin anhydride modified epoxy soybean oil, which significantly enhances the compatibility of the three interfacial bonding strength. The nitrile rubber itself has excellent toughness, and the aramid fiber has the characteristics of high strength and high modulus, so that the nitrile rubber and aramid fiber play an excellent toughening and strengthening role, so that the composite material has higher impact strength and flexural strength.
[0054] At the same time, rosin anhydride modified epoxy soybean oil contains flexible soybean oil molecular chains, which can also play a toughening effect on phenolic resin, further improving properties such as toughness and impact strength; and it contains heat-resistant rosin condensed ring structure, and chemically grafts and bonds the rosin condensed ring structure to the side chain of phenolic resin, which has a significant effect on improving the thermal decomposition temperature and high-temperature mass residual rate of phenolic resin. At the same time, a chemical cross-linking network is formed between phenolic resin and high-temperature resistant aramid fiber, which increases the cross-linking degree between molecular chains and can further improve the high-temperature resistance of the composite material.
[0055] Comparative Example 1 does not add rosin anhydride modified epoxy soybean oil, resulting in the inability to form chemical bonds between the hydroxyl-terminated liquid nitrile rubber, plasma-modified aramid fiber and phenolic resin, the compatibility interface bonding strength between the three is low, and the strengthening and toughening effect of the nitrile rubber and aramid fiber is not good. At the same time, the heat-resistant rosin condensed ring structure is not grafted into the phenolic resin, and the thermal decomposition temperature of the composite material is low.
[0056] Comparative Example 2 uses rosin maleic anhydride adduct to replace rosin anhydride modified epoxidized soybean oil. Rosin maleic anhydride adduct contains only one anhydride group, and one rosin maleic anhydride adduct molecule cannot react with the hydroxyl-terminated liquid nitrile rubber, modified aramid fiber and phenolic resin at the same time, and no chemical bonding can be formed between the three. The impact strength and flexural strength of the composite material are lower than those in Example 1.
[0057] Comparative Example 3 uses epoxy soybean oil instead of rosin anhydride modified epoxy soybean oil. It does not contain active anhydride groups, and is difficult to react with hydroxyl liquid nitrile rubber, modified aramid fiber and phenolic resin. The compatibility interface bonding strength between the three is low, and the strengthening and toughening effect of nitrile rubber and aramid fiber is not good. At the same time, epoxy soybean oil does not contain the heat-resistant rosin condensed ring structure. The impact strength, flexural strength and thermal decomposition temperature of the composite material are low.
[0058] Comparative Example 4 uses carboxyl-terminated liquid nitrile rubber instead of hydroxyl-terminated liquid nitrile rubber. Comparative Example 5 uses unmodified aramid fiber instead of plasma-modified aramid fiber. Both of them do not contain hydroxyl groups and cannot react with the anhydride group of rosin anhydride-modified epoxidized soybean oil, resulting in the inability of both to form chemical bonds with phenolic resin, poor interfacial bonding strength of compatibility, and the impact strength and other properties of the composite material are lower than those of Example 1.
Claims
1. A method for preparing a high temperature resistant toughened polymer composite material, characterized in that: The high temperature resistant toughened polymer composite material comprises the following raw materials by weight: 60-86 parts of phenolic resin, 8-20 parts of hydroxyl-terminated liquid nitrile rubber, 4-15 parts of rosin anhydride modified epoxy soybean oil, and 2-5 parts of plasma modified aramid fiber; The preparation method of the high temperature resistant toughened polymer composite material is as follows: phenolic resin, hydroxyl-terminated liquid nitrile rubber, rosin anhydride modified epoxy soybean oil, and plasma modified aramid fiber are added into a high-speed mixer, and after mixing, the materials are poured into a mold for co-curing to obtain the high temperature resistant toughened polymer composite material.
2. The method for preparing the high temperature resistant toughened polymer composite material according to claim 1, characterized in that: The mixing temperature is 50-70° C., and the mixing time is 1-3 hours.
3. The method for preparing the high temperature resistant toughened polymer composite material according to claim 1, characterized in that: The co-curing is firstly cured at 80-90°C for 2-5h, then cured at 100-120°C for 2-3h, and finally cured at 130-150°C for 2-3h.
4. The method for preparing the high temperature resistant toughened polymer composite material according to claim 1, characterized in that: The preparation method of the rosin anhydride modified epoxy soybean oil comprises the following steps: adding rosin maleic anhydride adduct and catalyst tetrabutylammonium bromide into the epoxy soybean oil, stirring and mixing, reacting, cooling and discharging the material, and obtaining the rosin anhydride modified epoxy soybean oil.
5. The method for preparing the high temperature resistant toughened polymer composite material according to claim 4, characterized in that: The reaction temperature is controlled at 90-100° C. During the reaction, the acid value is measured every 1 hour, and the reaction is terminated when the acid value of the reaction system is 6-8 mg / KOH.
6. The method for preparing the high temperature resistant toughened polymer composite material according to claim 4, characterized in that: The masses of the rosin maleic anhydride adduct and tetrabutylammonium bromide are 165-205% and 1.4-2% of the mass of the epoxidized soybean oil respectively.
7. The method for preparing the high temperature resistant toughened polymer composite material according to claim 1, characterized in that: The preparation method of the plasma-modified aramid fiber is as follows: placing the aramid fiber in a reaction chamber of a cold plasma generator, evacuating the reaction chamber and then introducing air, controlling the pressure to be 40-70 Pa, and then adjusting the output power of a plasma power supply to perform plasma treatment to obtain the plasma-modified aramid fiber.
8. The method for preparing the high temperature resistant toughened polymer composite material according to claim 7, characterized in that: The output power of the plasma power supply is 60-120W, and the plasma treatment time is 2-6min.
Citation Information
Patent Citations
Oil soluble thickening agent, production method and application in producing pesticide missible oil thereof
CN101401571A
Preparation of thermosetting polymer high in biological base content
CN105837796A
Toughening type phenolic resin and preparation method thereof
CN109971120A
